Management of the Economic Capacity of the Region on the Basis of Foresight (on the Example of Adygea, Russia) - Zakharova, Elena Nikolaevna; Kardava, Elena Evgenyevna; Avanesova, Rita Rafaelovna; Avramenko, Elena Petrovna (International Journal of Economics and Financial Issues, 2015)
In connection with the aggravation of crisis phenomena in the economy of Russia caused by the events in Ukraine, the sanctions of the West, oil prices reduction and a decline in the ruble, a new approach to strategic planning is required. Foresight technology is the most appropriate one. The purpose of this article is to give a brief description of the foresight as a technology of foreseeing and identifying the most promising points of regional capacity, aimed at improving the competitiveness on the example of a particular region of the Russian Federation – the Republic of Adygea. The authors note that conducting the regional foresight project must be preceded by an analysis of economic, natural, innovative, and information- technological capacity of the region. The article reviews the methods for foresight, gives the characteristics of natural, economic, innovation and information- technological capacity of the Republic of Adygea. In the article the development problems of the region, uncertainty factors and trends of socio-economic changes in the republic have been identified. The implementation of the foresight project will allow to form the basis for social partnership of government, business and social community in order to better exploit opportunities and the implementation of the economic capacity of the region. Keywords: foresight, forecasting, anticipation, socio-economic development, regional capacity, long-term strategy, uncertainty. JEL Classifications: D81; O18